Penerapan Pembelajaran Berdiferensiasi dengan Model PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Kelas 2 SDN Panggung Lor - Fitriani, Sinta; Mudzanatun , Mudzanatun; Kusuma , Rimba (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Students' problem-solving abilities are used as a fundamental perspective in mathematics learning. The aim of this research is to improve the problem solving abilities of students at SDN Panggung Lor Semarang with differentiated learning using the PBL model. This research is classified as classroom action research (PTK) with subjects of 26 grade 2 students for the 2023/2024 academic year. Data was collected based on written test techniques and observations. The technique used is qualitative descriptive analysis. Based on classroom action research, it shows that there is an increase in students' problem solving abilities after implementing differentiated learning with the PBL model. Pre cycle 38.46, became 61.53 in cycle 1 and rose to 90.38 in cycle 2. The indicator for planning problem solving experienced an increase in the average score for each cycle, from pre cycle 30.76 to 53.84 in cycle 1 and increased by 78.2 in cycle 2. The indicator of implementing the plan experienced an increase in the average score for each cycle, from pre-cycle 57.69 to 80.76 in cycle 1 and rose to 90.38 in cycle 2. Checking Indicators the answers experienced an increase in the average score for each cycle, from pre-cycle 28.84 to 40.38 in cycle 1 and increased by 61.53 in cycle 2. (2) The percentage of student completion reaching KKM 75 before the action was 46%, at the end of the cycle it increased to 78%.